GREEN FINANCE AND SUSTAINABLE DEVELOPMENT IN UZBEKISTAN: THE ROLE OF ESG AND GREEN BONDS IN EMERGING MARKETS (Scientific journal of the Fergana State University, 2026)
This article analyzes the role of green finance in Uzbekistan’s sustainable development process, as well as the implementation of ESG (environmental, social, and governance) principles and the formation of the green bond market. The study compares the country's regulatory framework, institutional readiness, and market opportunities with international practices. The results indicate that Uzbekistan has the potential to become a regional leader in implementing green finance instruments; however, it must address several systemic challenges, including improvements in the legal framework, institutional capacity, and investor awareness.